The Magnitude of the 39.8 ka Campanian Ignimbrite Eruption, Italy: Method, Uncertainties and Errors - Silleni, Aurora; Giordano, Guido; Isaia, Roberto; Ort, Michael H. (Frontiers in Earth Science, 2020)
The 39.8 ka Campanian Ignimbrite eruption is the largest caldera-forming eruption of the Campi Flegrei and had a global-scale impact on the environment and human populations. The cooling following the eruption and its widespread tephra strongly affected the paleoenvironment and the migration of hominids in Europe. Despite a large number of studies, the Campanian Ignimbrite Dense Rock Equivalent (DRE) volume estimates range from 60 to 300 km3. Here we present a review of the previous volume evaluations and a new calculation of the volume of the ignimbrite. This estimate is constrained by the first total isopach map of the Campanian Ignimbrite PDC deposit preserved on land, developed through a method that reconstructs the paleo-topography at the time of the eruption. The method is reproducible for all strongly topographically controlled ignimbrites and allows the calculation of well-defined uncertainties in the on-land ignimbrite deposits. The preserved total extra-caldera bulk volume of the ignimbrite is estimated at 68.2 km3 ± 6.6 km3. The total PDC deposit volume is then corrected for erosion, ash elutriation, the intracaldera deposit volume and the volume of tephra deposited in the sea, and volumes of fallout are taken from other studies. The final total volume estimate of the eruption ranges from 177 km3 – 265 km3 DRE. This value corresponds to a mass of 4.6 - 6.9 x 1014 kg, a magnitude (M) of 7.7 – 7.8 and a volcanic explosivity index (VEI) of 7. The new detailed estimate of the Campanian Ignimbrite eruption physical parameters, for the first time constrained by the ignimbrite deposit, confirms the magnitude of this event.